Presence of Malassezia Species in Patients Admitted to the Neonatal Intensive Care Unit and Antifungal Sensitivity of Malassezia furfur - Mehmet OKUL; Özmert Muhammet Ali ÖZDEMİR; Hacer ERGİN; Çağrı ERGİN (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Prophylactic administration of fluconazole in very low birth weight newborns (<1,500 g) in the neonatal intensive care unit (NICU) greatly reduces the incidence of fungal infections. However, the number of cases of neonatal fungemia caused by Malassezia furfur (M. furfur), a lipid-dependent species of Malassezia, is increasing. The presence of antifungal resistance among yeasts may also cause treatment failure. Thus, we aimed to evaluate the rate of skin colonization by Malassezia species, factors associated with its colonization, and antifungal sensitivities of M. furfur strains in our hospital’s NICU. Materials and Methods: This study included 150 newborns admitted to the NICU. Swabs of the skin surface were collected on the day of hospitalization and inoculated on mDixon agar which was incubated for one week. Conventional tests and MALDI-ToF analysis were used to identify Malassezia species. Antifungal susceptibility tests were performed using RPMI-1640 medium enriched with fatty acids and resazurin (RPMI++). Results: Malassezia species colonization was detected in 33.3% of the included newborns (n=50). M. furfur was the most frequently isolated strain (n=16, 32.0%), followed by Malassezia sympodialis (n=13, 26.0%), Malassezia restricta (n=9, 18.0%), Malassezia obtusa (n=6, 12.0%), and Malassezia globosa (n=6, 12.0%). M. furfur was isolated from 12 (19.04%) newborns receiving total parenteral nutrition (n=63) (p<0.05). Malassezia species colonization was observed in 39.2% of the fluconazole-naïve neonates and 10% of the infants in the prophylaxis group (p<0.05). Fluconazole demonstrated a high MIC90 value (32 µg/ml) for M. furfur strains. Conclusion: Malassezia-associated infections may be masked because microbiological cultures for Malassezia species are not frequently performed. Thus, screening for Malassezia species in newborns admitted to NICUs and determining its antifungal resistance patterns will aid in establishing treatment procedures.